Exploring the Role of ChatGPT in Developing Writing Skills and Critical Thinking among Vocational High School Students - Rohmatul Janah; Tusino Tusino; Puspa Dewi (AL-ISHLAH: Jurnal Pendidikan, 2026)
The rapid growth of generative artificial intelligence (AI), particularly ChatGPT, has introduced new possibilities for language learning through interactive feedback and writing assistance. Despite its increasing use in education, empirical evidence remains limited regarding its pedagogical role in vocational secondary schools, particularly in distinguishing its support for surface-level writing skills from deeper reasoning processes. This study investigated how ChatGPT integration could enhance students’ writing skills, foster reasoning, and influence student perceptions in a vocational high school context. This research employed a qualitative Classroom Action Research (CAR) design conducted in two cycles with 32 eleventh-grade students at SMK YPE Sawunggalih Kutoarjo, Indonesia. Data were collected through classroom observations, writing tasks, semi-structured interviews, and student reflective journals. The data were analyzed thematically, while students’ writing performance was evaluated using a rubric focusing on organization, grammar, vocabulary, and argumentation. The findings indicated consistent improvements in students’ vocabulary, grammar, and organization across the two cycles, with vocabulary showing the most notable development. Students reported that ChatGPT was useful and motivating during the writing process. However, its contribution to argumentation and critical thinking remained relatively limited. Benefits included faster idea generation and greater engagement in revision activities, while challenges involved students’ overreliance on AI-generated responses and limited skills in designing effective prompts. ChatGPT can function as an effective linguistic scaffold for supporting surface-level writing development. However, its impact on deeper reasoning and argumentation depends on structured teacher mediation and reflective instructional design. This study provides empirical evidence from a vocational secondary education context and highlights the conditions under which generative AI supports different dimensions of writing development.